Verticillium longisporum Elicits Media-Dependent Secretome Responses With Capacity to Distinguish Between Plant-Related Environments - Leonard, Miriam; Kühn, Anika; Harting, Rebekka; Maurus, Isabel; Nagel, Alexandra; Starke, Jessica; Kusch, Harald; Valerius, Oliver; Feussner, Kirstin; Feussner, Ivo; Kaever, Alexander; Landesfeind, Manuel; et al. (Frontiers in Microbiology, 2020)
Verticillia cause a vascular wilt disease affecting a broad range of economically valuable crops. The fungus enters its host plants through the roots and colonizes the vascular system. It requires extracellular proteins for a successful plant colonization. The exoproteomes of the allodiploid Verticillium longisporum upon cultivation in different media or xylem sap extracted from its host plant Brassica napus were compared. Secreted fungal proteins were identified by label free liquid chromatography-tandem mass spectrometry screening. V. longisporum induced two main secretion patterns. One response pattern was elicited in various non-plant related environments. The second pattern includes the exoprotein responses to the plant-related media, pectin-rich simulated xylem medium and pure xylem sap, which exhibited similar but additional distinct features. These exoproteomes include a shared core set of 221 secreted and similarly enriched fungal proteins. The pectin-rich medium significantly induced the secretion of 143 proteins including a number of pectin degrading enzymes, whereas xylem sap triggered a smaller but unique fungal exoproteome pattern with 32 enriched proteins. The latter pattern included proteins with domains of known pathogenicity factors, metallopeptidases and carbohydrate-active enzymes. The most abundant proteins of these different groups are the necrosis and ethylene inducing-like proteins Nlp2 and Nlp3, the cerato-platanin proteins Cp1 and Cp2, the metallopeptidases Mep1 and Mep2 and the carbohydrate-active enzymes Gla1, Amy1 and Cbd1. Their pathogenicity contribution was analyzed in the haploid parental strain V. dahliae. Deletion of the majority of the corresponding genes caused no phenotypic changes during ex planta growth or invasion and colonization of tomato plants. However, we discovered that the MEP1, NLP2 and NLP3 deletion strains were compromised in plant infections. Overall, our exoproteome approach revealed that the fungus induces specific secretion responses in different environments. The fungus has a general response to non-plant related media whereas it is able to fine-tune its exoproteome in the presence of plant material. Importantly, the xylem sap-specific exoproteome pinpointed Nlp2 and Nlp3 as single effectors required for successful V. dahliae colonization.